PENGARUH PEMBELAJARAN KEWIRAUSAHAAN DAN MOTIVASI TERHADAP MINAT BERWIRAUSAHA SISWA DENGAN SELF EFFICACY SEBAGAI VARIABEL INTERVENING - Asep munawar, - (2019)
The problem studied in this study is the low level of interest of students in entrepreneurship in SMK Negeri Purwakarta. The interest in entrepreneurship can also be understood as a spirit that grows from oneself without any coercion from others. The role of entrepreneurship learning and motivation with self efficacy is used as a way to increase interest in student entrepreneurship. This study aims to determine the effect of entrepreneurial learning and motivation on the interests of student entrepreneurship with self efficacy as an intervening variable, as well as how much influence entrepreneurial learning and motivation influence students' interest in entrepreneurship with self efficacy as an intervening variable. This research was conducted by explanatory survey method. The design used in this study is cross sectional design by means of a single cross sectional method. The population in this study were students of Vocational Schools throughout Purwakarta with a total of 12 schools. The technique used in this sampling uses the Two Stage Cluster Random Sampling technique and selected 4 schools with a total sample of 299 respondents. Data were analyzed using Structural Equation Modeling (SEM) with AMOS 5 program with maximum likelihood estimation. The results of the study show that 1) Entrepreneurial learning has an effect on Self efficacy, 2) Motivation has an effect on Self efficacy, 3) Self efficacy influences students' entrepreneurial interest, 4) Entrepreneurship learning influences students' interest in entrepreneurship and 5) Motivation does not affect the interest in student entrepreneurship;---Permasalahan yang dikaji didalam penelitian ini adalah rendahnyatingkat minat siswa untuk berwirausaha di SMKN Se-kabupaten purwakarta.Minat berwirausaha juga dapat dipahami sebagai semangat yang tumbuh dari diri sendiri tanpa ada paksaan dari orang lain. Peran pembelajaran kewirausahaan dan motivasi dengan self efficacydijadikansebagaisuatu cara untukmeningkatkan minat berwirausaha siswa.Penelitian ini bertujuan untuk mengetahuipengaruh pembelajaran kewirausahaan dan motivasi terhadap minat berwirausaha siswa dengan self efficacysebagai variabel intervening, sertaseberapa besar pengaruh pembelajaran kewirausahaan dan motivasi terhadap minat berwirausaha siswa dengan self efficacysebagai variabel intervening.Penelitian ini dilakukan dengan metode survey explanatory.Desain yang digunakan dalam penelitian ini adalah cross sectional design dengan cara single cross sectional method.Populasi dalam penelitian ini adalah siswa SMKN se-kabupaten purwakarta dengan jumlah 12 sekolah. Teknik yang digunakan dalam pengambilan sampel ini menggunakan teknik Two Stage Cluster Random Samplingdan terpilih 4 sekolah dengan total sampel 299 responden.Data dianalisis dengan menggunakan Structural Equation Modelling (SEM)dengan program AMOS 5 dengan maximum likelihood estimation.Hasil penelitian menunjukkan bahwa 1) Pembelajaran kewirausahaan berpengaruhterhadap Self efficacy, 2) Motivasi berpengaruh terhadap Self efficacy, 3) Self efficacyberpengaruh terhadap minat berwirausaha siswa, 4) Pembelajaran kewirausahaan berpengaruh terhadap minat berwirausaha siswa dan 5) Motivasitidakberpengaruhterhadap minat berwirausaha siswa.